The relationship between dental caries and stunting among children in a rural Indonesian Subdistrict: Evidence from Krueng Barona Jaya, Aceh Besar - Diana Setya Ningsih; Nani Safuni; Subhaini Subhaini; Rahma Annisa (AcTion: Aceh Nutrition Journal, 2025)
Stunting is a significant global health issue and is particularly prevalent in certain regions, including the Krueng Barona Jaya Subdistrict, Aceh Besar, Indonesia. One contributing factor to stunting is inadequate nutrient intake, which may be linked to oral health problems such as dental caries that impair a child’s ability to chew and consume food. This study aimed to analyze the relationship between dental caries and stunting in children aged 0 – 5 years in Krueng Barona Jaya. A cross-sectional study involving 44 children was conducted between July and October 2024. Anthropometric measurements were taken using the WHO child growth standards to assess nutritional status, and dental caries were recorded using the decayed, missing, and filled teeth (DMFT) index and assessed based on criteria established by the International Caries Detection and Assessment System (ICDAS). The results showed that 54,5% of the stunted children had to 1-3 caries (33,3%) or more than six caries (29,2%), with (79,2%) classified as having a high risk of caries.  Statistical analysis revealed a significant relationship between the number of carious teeth (p=0,006) and caries risk level (p=0,013) with stunting. These findings suggest that dental caries and a high caries risk may contribute to poor nutritional outcomes in early childhood, increasing the likelihood of stunting. Therefore, early prevention and management of dental caries are essential for reducing the prevalence of stunting.